Комплексная утилизация свалочного газа полигонов твердых бытовых отходов Украины - Жук, Г.В.; Пятничко, А.И.; Кубенко, С.Б.; Иванов, Ю.В.; Крушневич, С.П.; Федоренко, Д.С. (Энерготехнологии и ресурсосбережение, 2015)
Проведен системный анализ полигонов твердых бытовых отходов крупных городов Украины. Разработаны научные основы и методология создания систем утилизации биогаза в энергетических установках, а также комплексные технологии сбора, подготовки и использования биогаза с выработкой электроэнергии, тепла, биометана (аналога природного газа) и углекислоты, их хранения и поставки потребителям в виде гидратов беструбопроводным транспортом. Разработаны проекты и внедрены на полигонах твердых бытовых отходов промышленные комплексы по защите атмосферы от парниковых газов, их утилизации с выработкой электроэнергии общей мощностью 5,2 МВт для централизованной электросети. Проведено системний аналіз полігонів твердих побутових відходів великих міст України. Розроблено наукові засади та методологію створення систем утилізації біогазу в енергетичних установках, а також комплексні технології збору, підготовки та використання біогазу з виробленням електроенергії, тепла, біометану (аналога природного газу) та вуглекислоти, їх зберігання та постачання споживачам у вигляді гідратів безтрубопровідним транспортом. Розроблено проекти та впроваджено на полігонах твердих побутових відходів промислові комплекси захисту атмосфери від парникових газів, їх утилізації з виробленням електроенергії загальною потужністю 5,2 МВт для централізованої електромережі. Handling solid waste (MSW), including their derivatives — landfill gas and leachate, today takes on strategic importance. Currently landfills in Ukraine do not have short-term alternatives for the disposal of waste received annually in an amount of 12–13 billion tons Landfills are located throughout the country near cities and work as reactors emit into the atmosphere methane-inclusive combustible gas in the volume of 1 billion m3 per year. Gas Institute of NAS of Ukraine is the leading research institution in Ukraine developing processing and utilization technologies of landfill gas. Based on a systematic analysis of major cities landfills scientific principles and methodology of biogas generation and utilization in power plants were developed, a complex technology was developed of gathering, processing and use of biogas to power generation and biomethane fuel (similar to natural gas) producing, and carbon dioxide storage, and pipeless transport supplies to consumers in the form of hydrates. Averaged results of chemical analysis indicate a high content of methane (50 %) in the landfill gas, which corresponds to net calorific value of 20–25 MJ/Nm3. High fuel capacity of landfill biogas can effectively use it instead of natural gas in power plants and vehicles, for its gas supply network in Ukraine. Projects were developed and implemented at landfills of Ukraine, industrial complexes protect the atmosphere of greenhouse gases and make their utilization with power generation of 5,2 MW total for centralized power supply.